Textbooks and the legitimization of equality. (Journal of Parents and Teachers, 2014)
Textbooks play an important role in the teaching and learning process: they show the norms and values of our society. A critical attitude towards the choice of textbooks must be maintained, so that they are adequate and promote equality.
Keywords: Textbooks; critical choice; promotion of equality.